Home-based care: barriers and facilitators to expanded personal support worker roles in Ontario, Canada. Issue 3 (2nd October 2017) - Saari, Margaret; Patterson, Erin; Killackey, Tieghan; Raffaghello, Julia; Rowe, Alissa; Tourangeau, Ann E
ABSTRACT: To accommodate the increasing demand for home care in Ontario, Canada, some care tasks traditionally performed by regulated health professionals are being transferred to personal support workers (PSW). However, this expansion of PSW roles is not uniform across the province. Between December 2014 and April 2015, barriers and facilitators to expansion of PSW roles in home care were explored in a series of 13 focus groups. Home care staff identified seven categories of factors affecting the expansion of PSW roles in home care including: communication and documentation; organization and structures of care; attitudes and perceptions of the expanding PSW role; adequate staffing; education, training and support; PSW role clarity and variation in practices, policies, and procedures. Addressing barriers and promoting facilitators at the funder and employer levels will enable the provision of safe, effective, and equitable care by PSWs.